The Pengaruh Financial Knowledge, Locus Of Control, Dan Financial Literacy Terhadap Financial Management Behavior - Khakimah, Okky Aliyatul; Handayani, Anita (Jurnal Mahasiswa Manajemen, 2023)
Background – Indonesia is a developing country that has high economic potential. This very rapid economic development has a strong connection with the industrial world. The current economic development has an impact on society, especially micro, small and medium enterprises. Therefore, the rapid emergence of MSMEs must be balanced with good financial knowledge and financial literacy so that they can make decisions based on the financial behavior of each MSME actor. The current conditions that occur in Indonesian society tend to have consumerist financial behavior, meaning that Indonesian people lack a sense of responsibility for their financial behavior. This is caused by several factors such as lack of saving, investment, and emergency planning. Objectives – This research aims to test financial management behavior. The influence of financial knowledge, locus of control, and financial literacy on financial management behavior among MSMEs assisted by the Gresik Regency Transportation Service. Design / methodology / approach – Testing was carried out using multiple linear regression analysis. The method used is the quantitative method. Data analysis uses SmartPLS 3.0 using 56 samples of MSME actors to analyze the level of financial knowledge, financial control and understanding of financial literacy in the MSME trading sub-sector under the guidance of the Gresik Regency Transportation Service. Findings – The regression results show that financial knowledge has a significant effect on financial management behavior. Locus of Control has a significant effect on financial management behavior, but financial literacy does not have a significant effect on financial management behavior. This research can be used by financial institutions and the government in reviewing the development of MSMEs in Indonesia Research implication – Partially, there is empirical evidence that financial knowledge has a significant effect on financial management behavior. Partially, there is empirical evidence that locus of control has a significant effect on financial management behavior. Partially, there is empirical evidence that financial literacy does not have a significant effect on financial management behavior. The influence represented by the coefficient of determination test results shows that the ability of the independent variable to explain the financial management behavior variable is 98.1%, while the remaining 11.9% is influenced by other factors outside the research model. Limitations – This research has limited digital knowledge in the Human Resources (HR) of MSME actors, where data collection still uses conventional systems but does not use digital platforms.